The Usborne book of famous paintings - Dickins, Rosie; Hopman, Philip (London : Usborne ; Tulsa, Okla. : EDC, 2009)
Introduces thirty-five famous paintings, including a reproduction of each piece accompanied by a simple analysis of the work.
Includes index.
6.7
3-6.
3-6
Keywords: Art appreciation -- Juvenile literature; Painting -- Appreciation -- Juvenile literature; Art appreciation; Painting -- Appreciation; Art appreciation; Painting